Gay Men's Understanding and Education of New HIV Prevention Technologies in Vancouver, Canada. (October 2017) - Klassen, Benjamin J.; Lachowsky, Nathan J.; Lin, Sally Yue; Edward, Joshua B.; Chown, Sarah A.; Hogg, Robert S.; Moore, David M.; Roth, Eric A.
Effective rollout of HIV treatment-based prevention such as pre-exposure prophylaxis and treatment as prevention has been hampered by poor education, limited acceptability, and stigma among gay men. We undertook a thematic analysis regarding the education sources and acceptability of these New Prevention Technologies (NPTs) using 15 semistructured interviews with gay men in Vancouver, Canada, who were early adopters of NPTs. NPT education was derived from a variety of sources, including the Internet, health care providers, community organizations, sexual partners, and peers; participants also emphasized their own capacities as learners and educators. Acceptable forms of NPT education featured high-quality factual information, personal testimony, and easy access. Stigma was highlighted as a major barrier. For public health, policy makers, and gay communities to optimize the personal and population benefits of NPTs, there is a need for increased community support and dialogue, antistigma efforts, early NPT adopter testimony, and personalized implementation strategies.